Comparison of water quality and habitat assessment between wetland and river - Mokhtar Kamal, Nurul Hana (2009)
River management trend nowadays always concentrate on beautifying and aesthetical improvement along a small stretch that is considered polluted; without taken into consideration the affect of water flowing from the watershed. Previously, the main concern was the functional uses of a stream such as erosion control where quite often the biotic factors of a river are overlooked. Furthermore, wetlands are usually drained as they hold great potentials to be transformed into agricultural land without considering the impact to the wetland values and functions. Thus, this study intends to emphasize on the importance of habitats and fish species to be implemented on river and wetland rehabilitation studies. Three rivers with different physical condition and land uses were selected for habitat assessment; i.e. Sungai Lukah Wetland in Ulu Sedili Kecil, Sungai Tui in Bukit Kepong, and Sungai Mengkibol in Kluang. Sungai Lukah, which is a part of freshwater swamp area of Ulu Sedili Kecil was classified as Class III using Water Quality Index (WQI). Regardless of the water quality, the swampy area of Sungai Lukah provides a suitable environment for swamp fishes that was dominated by Cyprinidae as they exist in abundance. Besides the importance of hydrological and biogeochemical function of Lukah wetland, it also provides food, spawning ground and protection from predators for the aquatic ecosystem. In contrast, Sungai Tui, which is a tributary from Sungai Muar, eventhough classified as Class III in WQI, provides a rich and diverse fish and crustaceans communities with high commercial value such as Udang Galah. On the other hand, Sungai Mengkibol which was classified in Class IV served as main storm drain for Kluang town and is only inhabited by hard and tolerant species.